DOES ISLAMIC FINANCE DRIVE ECONOMIC GROWTH IN INDONESIA? AN ANALYSIS USING VECTOR ERROR CORRECTION MODEL - Kurniawan, Eko; Rani, Lina Nugraha; Pertiwi, Tanza Dona (Jurnal Ekonomi dan Bisnis Airlangga, 2025)
Introduction: Indonesia, as the second-largest Muslim-majority country in the world, has significant potential for developing the Islamic finance sector. On the other hand, the financial sector, including Islamic finance, plays a crucial role in a country's economic growth. Methods: This study utilizes quarterly time-series data from 2011 to 2023, with economic growth (GDP) as the dependent variable. The independent variables include Islamic banking assets, outstanding sukuk value, and total zakat distribution. The analysis is conducted using the vector error correction model (VECM), beginning with stationarity testing, optimal lag selection, cointegration testing, model estimation, and variance decomposition analysis. Results: The analysis results indicate that, in the short term, Islamic finance (Islamic banking, sukuk, and zakat) does not have a significant impact on Indonesia's economic growth. However, in the long term, these three variables have a positive and significant effect on economic growth. Conclusion and suggestion: Islamic finance has been proven to play an essential role in driving Indonesia's long-term economic growth. Islamic banking contributes through real sector financing; sukuk supports infrastructure development, and zakat enhances societal welfare and aggregate consumption. The government needs to strengthen Islamic financial infrastructure, improve financial literacy, and enhance the inclusivity of Islamic finance in Indonesia.